Mobilidade urbana : análise, compreensão e perspectivas para Rondonópolis/MT - Rodrigues, Oziel Milton (2015)
This research, in its general goal, has the purpose of analyze and consequently has an understanding of urban mobility and accessibility and their impact on the city of Rondonópolis / MT. For this, it was observed that the Federal Law No. 12,587 (Statute of Urban Mobility) is being put into practice in the city with regard to public transport and nonmotorized. Analyzed by tracing the lines of public transportation, if they meet the necessities of the population that uses them. We seek to synthesize all aspects presented in the survey through the case study. We use multiple data sources and diverse collection methods: direct and indirect observations, interviews, questionnaires, stories, audio and video records, letters, maps, documents, and more. Interviews were conducted during the months of March and April 2015 with the purpose of collecting data to get the results proposed in the goals. We noticed that the National Law on Urban Mobility is not applied in the city, for the collective transport by bus and non-motorized is not a priority in the city. It can make the city accessible from the point of view of urban mobility. It's a matter of planning and respect for the universal rights of accessibility and urban mobility.